2005
DOI: 10.1037/1076-8998.10.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Are Trends in Work and Health Conditions Interrelated? A Study of Swedish Hospital Employees in the 1990s.

Abstract: Swedish hospital personnel were followed over an 8-year period, characterized by staff redundancies and restructuring processes. Self-rated and administrative data sets from 1994 to 2001 allowed for studying long-term consequences of organizational instability for staff health and work conditions. The aim was to identify, on a work-unit level, trends in work and health conditions and their interdependence. Regression analysis showed a downward trend in mental health and an upward trend in long-term sick leave.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…As pointed out above, many of the previous studies on social support during organizational changes have focused on a lack of social support (Niedhammer et al, 2006;Petterson et al, 2005;Vahtera et al, 2000) or reported on how social networks within the workplace are disrupted and social cohesion is lost following downsizing (Campbell & Pepper, 2006;Koeber, 2002;Shah, 2000). This study shows similar findings, but only in departments where the psychosocial work environment was poor prior to the changes or for employees transferred to a new department.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As pointed out above, many of the previous studies on social support during organizational changes have focused on a lack of social support (Niedhammer et al, 2006;Petterson et al, 2005;Vahtera et al, 2000) or reported on how social networks within the workplace are disrupted and social cohesion is lost following downsizing (Campbell & Pepper, 2006;Koeber, 2002;Shah, 2000). This study shows similar findings, but only in departments where the psychosocial work environment was poor prior to the changes or for employees transferred to a new department.…”
Section: Discussionsupporting
confidence: 74%
“…Such quantitative studies have shown mixed results regarding health outcomes. Some have demonstrated that employees with low levels of social support are at increased risk for worse health and well-being during the changes (Niedhammer, Chastang, David, Barouhiel, & Barrandon, 2006;Petterson, Hertting, Hagberg, & Theorell, 2005;Vahtera et al, 2000). Other studies have demonstrated no effect of low social support during organizational changes on health and well-being outcomes (Lavoie-Tremblay et al, 2010).…”
Section: Organizational Changes and Social Supportmentioning
confidence: 99%
“…Previous research [17][18][19][20][21] has demonstrated links between adverse work conditions, health, and sickness absence, but has not examined the theoretical ordering or a causal pathway between them. We propose that health problems mediate the relationship between work conditions and sickness absence and our analysis identifies the likely mechanisms through which adverse work conditions affect sickness absence.…”
Section: Mediating Modelsmentioning
confidence: 99%
“…18,25,26 In the Whitehall study, employees who had more say in important work decisions (high control) had lower rates of both short and long-term sickness absence. 25 In the research we have reviewed, [17][18][19][20][21] we have not found any studies that have tested whether associations of sickness absence with insecurity and high work demands are mediated by mental or physical health. Mediating relationships are those in which the association between an exposure and an outcome might be partly or fully accounted for by an intermediary variable in a model (see Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation